Indian government and politics - Abbas, Hoveyda; Ranjay Kumar; Alam, Mohammed Aftab (New Delhi, 2011)
Framed within a perspective of the entire political process, this book closely examines the legal provisions of the Constitution of India, as well as the role and functions of other agencies and groups that influence policies and laws. It also looks at historical and contemporary cases to illuminate the philosophy behind the Constitution, the role of various social groups, the functioning of the government and the evolution of our politics. Written in a lucid and familiar style, this book assumes no background in the subject and an extensive glossary explains unfamiliar terms and complex concepts.
Keywords: Public Administration